Perancangan Timer Otomatis Mesin Lasting pada Proses Assembly Sepatu Sekolah Tomkins di PT. XYZ Menggunakan Metode Reverse Engineering Berdasarkan Analisis Menggunakan Pendekatan DMAI - Nadhifah, Nida Syifa; Lubis, Marina Yustiana; Nugrahaini, Yunita (LPPM Universitas Pahlawan Tuanku Tambusai, 2023)
PT XYZ is a company operating in the footwear industry. To be able to produce quality products, companies determine product CTQ so that a product is said to be a quality product. However, due to various factors, there are still products that do not meet the CTQ or are said to be defective products. To overcome this problem, the method used for analysis is the DMAI (Define, Measure, Analyze, and Improve) approach which is used to identify processes that are problematic and indicated to cause defective products, find out the factors that cause this to happen and find alternative solutions that are most likely to Next, the design and designing of the proposed tools is carried out using the reverse engineering method where the RE method focuses on developing existing products by adapting user needs. The proposed design of the auxiliary tool is an automatic timer that is integrated directly with the lasting machine and is connected to the timer in the lasting machine using a Programmable Logic Controller which will instruct that the gluing time on the front, side and back of the shoe is four seconds each. With the auxiliary tool This design proposal is expected to reduce the percentage of defects so that it does not exceed 1% by reducing the frequency of slanted lasting defects and upper defects (related to upper tears) and can increase the sigma value which is better than the existing condition.